Experiential Tourism in Palestinian Rural Communities : 'Abraham's Path' - Abukumail, Ali H. (World Bank, Washington, DC, 2013)
The economy of the Palestinian territories, hampered by years of conflict, occupation, and insecurity remains dependent on foreign aid with the public sector remaining the largest employer. However, it is critical that serious efforts are made to look at medium term measures that can reverse current negative trends and put the Palestinian economy on a path to sustainable growth. The Palestinian tourism industry has the necessary infrastructure, facilities and attractions to become a viable and independent destination. However, the industry is not developed fully across the value chain resulting in leakages of tourism revenue. Rural areas did not benefit from the recent growth, and were excluded from the mainstream tourism routes. In 2010, the Palestinian Ministry of Tourism and Antiquities (MOTA) released a national strategy that carried the vision of 'promoting the national image of Palestine as a safe, hospitable, independent destination, rich in religious, cultural, historical and natural resources'. The objectives of the master plan are to increase the number of visitors, diversify the type of visitors, increase the time and money spent in the host communities, and increase the geographical spread throughout the West Bank. Experiential tourism is a combination of adventure and community oriented tourism. Abraham's path is a route of walking and cultural tourism following the footsteps and memory of Abraham/Ibrahim across the Middle East.